2018
DOI: 10.1128/aac.01457-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antifungal Efficacy of Three New Cyclic Lipopeptides of the Class Bacillomycin from Bacillus subtilis RLID 12.1

Abstract: New lipopeptide homologues (AF, AF, and AF) with antifungal activities against and spp. were purified from a cell-free supernatant of RLID 12.1. The lipopeptides AF, AF, and AF were identified with the same peptide sequence Asn-Pro-Tyr-Asn-Gln-Thr-Ser with variations in the fatty acid branching type and chain length (-C, -C, and -C, respectively). Upon comparing the three homologues for MICs against 81 ( = 64) and ( = 17) clinical isolates and their cytotoxicities, we found that AF was the most promising antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 37 publications
1
35
0
2
Order By: Relevance
“…For commercial application of biologically active compounds, it is imperative to explore their toxigenic potential for the relevant applications. Though lipopeptides cause hemolysis (Inès and Dhouha, 2015;Greber et al, 2018;Ramachandran et al, 2018), surfactin-like lipopeptide in this study showed promising potential for topical applications as evident from the emulgel experiment. The gel showed antimicrobial activity and did not show any skin irritation effect during experiment with BALB/c mice.…”
Section: Discussionmentioning
confidence: 79%
“…For commercial application of biologically active compounds, it is imperative to explore their toxigenic potential for the relevant applications. Though lipopeptides cause hemolysis (Inès and Dhouha, 2015;Greber et al, 2018;Ramachandran et al, 2018), surfactin-like lipopeptide in this study showed promising potential for topical applications as evident from the emulgel experiment. The gel showed antimicrobial activity and did not show any skin irritation effect during experiment with BALB/c mice.…”
Section: Discussionmentioning
confidence: 79%
“…Polymyxin A is the example of lipopeptide with an antimicrobial activity which isolated from the soil bacterium Bacillus polymyxa [2]. Recently, several lipopeptides with diverse activities have been characterized, namely, as cytotoxic [3], antibacterial [4, 5], antifungal [6, 7], antiviral [8, 9], plant pathogenicity [10, 11], and anticancer [12, 13]. Some of them have been commercially used as an antibacterial drug such as daptomycin [14], caspofungin [15], micafungin [16], vancomycin, and teicoplanin [17].…”
Section: Introductionmentioning
confidence: 99%
“…The similar evidences were found in previous reports. 27,30 It was concluded that the antifungal compounds belonged to C 14 and C 15 of bacillomycin D homologues (C 14-15 BDs).…”
Section: Hplc-ms/ms Analysis Of the Antifungal Compounds 1 Andmentioning
confidence: 99%